2017
DOI: 10.1002/mp.12648
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic collimator trajectory algorithm for multiple metastases dynamic conformal arc treatment planning

Abstract: Dynamic collimator trajectories have the potential to improve DCA deliveries through increased efficiency, especially in the treatment of multiple cranial metastases. Implementation of this technology should not be hindered by mechanical safety considerations as collimator motions do not modify or introduce any new risks of collisions with patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 12 publications
0
42
0
Order By: Relevance
“…Another approach is including table rotation in the beam arrangements either at different static gantry angles or with a dynamic gantry rotation . Instead of including the table rotation also the collimator rotation can be taken into account to additionally increase the number of degrees of freedom . A further step, which is also the aim of this work, is to include both collimator and table rotation during beam delivery …”
Section: Introductionmentioning
confidence: 99%
“…Another approach is including table rotation in the beam arrangements either at different static gantry angles or with a dynamic gantry rotation . Instead of including the table rotation also the collimator rotation can be taken into account to additionally increase the number of degrees of freedom . A further step, which is also the aim of this work, is to include both collimator and table rotation during beam delivery …”
Section: Introductionmentioning
confidence: 99%
“…Selection of dynamic collimator angles for arc therapy based on patient anatomy has suggested previously, for example, by alignment of the MLC with the spinal cord for paraspinal treatments or based on conformance of the MLC to the target for treatments of multiple metastatic brain tumors . Our method, in contrast, is based on two tractable algorithms: convex fluence map optimization (FMO) followed by a linear network flow model to select a trajectory of collimator rotations.…”
Section: Introductionmentioning
confidence: 99%
“…: a statistically significant decrease of 34% in MUs (increase in MU efficiency) when compared to VMAT plans, and a statistically significant improvement of 14% in target coverage accuracy when compared to optimized DCA. A previous study by this group has demonstrated the potential advantages of collimator optimization in DCA treatments of multiple metastases. However, that study focused on single prescription multiple metastases cases.…”
Section: Discussionmentioning
confidence: 99%
“…The optimizer then computes the objective function by approximating total dose as the sum of all dose matrices. While this method ignores the presence of nontarget anatomy between targets that may be present in the final MLC apertures (potentially unavoidable due to relative target orientation, or potentially caused by mechanical constraints on collimator motions), the optimization of the collimator angle through dynamic collimator rotation minimizes discrepancies caused by this approximation . By computing this sum, the optimization does not require recalculation of dose with each modification to the aperture, as there are only two possible positions for the aperture: completely closed (zero) or set conformally (one).…”
Section: Discussionmentioning
confidence: 99%